Prebreeding research of near-isogenic lines of spring bread wheat with a combination of translocations from Agropyron elongatum (Host.) Р.В. and Aegilops ventricosa Tausch. - S. N. Sibikeev; A. E. Druzhin (Вавиловский журнал генетики и селекции)
To protect bread wheat from pathogens and, in particular, rust diseases, introgressive resistance genes located in alien translocations are commonly used. However, their application in practical breeding demands prebreeding studies. They reveal effects of translocations on the adaptive properties of plants, performance indices, yield, and the quality of the final product. For this purpose, we studied the L653 and L654 near-isogenic lines of spring bread wheat cultivar Dobrynya, resistant to leaf rust and carrying the combination of translocations 7DS • 7 DL-7Ae#1L + 2AL • 2AS-2MV#1, which host genes Lr19/Sr25 from Agropyron elongatum (Host.) P. B. and Lr37/Sr38/ Yr17 from Aegilops ventricosa Tausch. The recipient cv. Dobrynya and standard cv. Favorite were used as references. Phytopathological tests showed that L653 and L654 were highly resistant to Puccinia triticina at all stages of plant development and to Puccinia graminis race Ug99 + Lr24 (TTKST), but they were moderately susceptible to the Saratov population of this pathogen. The prebreeding research of lines L653 and L654 showed that the combination of 7 DS • 7 DL-7Ae#1L + 2AL • 2AS-2MV#1 translocations: (1) prolonged the seedling emergence –heading time by 7 days and increased the mean plant height by 10 cm; (2) did not affect lodging resistance or 1000 kernel weight; (3) affected grain yield in neither drought years nor years of leaf rust outbreaks; (4) reduced plant adaptation to abrupt vegetation condition changes; (5) reduced gluten amount without affecting its strength, dough tenacity, tenacity : extensibility ratio, flour strength, bread volume, or bread porosity. Thus, the combination of 7DS • 7 DL-7Ae#1L + 2AL • 2AS-2MV#1 translocations in the genotype of spring bread wheat cv. Dobrynya determines high resistance to leaf rust and stem rust race Ug99 + Lr24 (TTKST), being neutral with regard to agronomic performance indices.